Cost estimation related to drug waste in two major pediatric referral centers and one adult hospital in southern Iran: comparative cross-sectional study - Razieh Karamikhah; Dena Firouzabadi; Safoura Bahmani; Afsaneh Vazin (Shiraz University of Medical Sciences, 2018)
Purpose: children are a large group of patients receiving medications. Since pediatric dosageforms are generally not available, adult dosage forms have to be used for children instead, which leads to large amounts of drug wastage, and high costs are imposed on the healthcare system. This study was carried out to evaluate the amount of medication waste and the cost in pediatric wards of two major pediatric referral centers in southern Iran. The results were compared with an adult ward in the same hospital.Method: This comparative cross-sectional study was carried out during a three-month period, from April to June 2014, assigning one month to each ward. A trained pharmacist collected the data using direct observational method during morning shifts. All the drug preparation processes were evaluated by direct visual observation. During this supervision, factors involved in medication waste and also the dose of drug prescribed and wasted were evaluated.Results: The percent of medication waste in pediatric wards of Nemazee and "Shiraz Ghadir Mother and Child" hospital was 17.4% and 18.05%. The cost of wastage was estimated to be 568.11 USD and 368.11 USD for each hospital during one-month. According to the results, in pediatric wards of "Nemazee" and "Shiraz Ghadir Mother and Child" hospitals 101 out of 290 and 45 out of 80 prescriptions consisted of at least one antibiotic. In both hospitals the most prescribed antibiotic was vancomycin.Conclusion: The results indicated that medication waste in pediatric ward of Nemazee hospital was not significantly different in comparison with pediatric ward of Shiraz Ghadir Mother and Child hospital, but the waste was calculated to be more in the pediatric ward in comparison with the adult ward of Nemazee hospital. The most wasted group of medication was reported to be antibiotics. Vancomycin was reported to have the highest consumption and gentamicin was the leading wasted medication.